Relevancia en el reconocimiento del costo de los inventarios fiscalmente en Colombia, teniendo en cuenta sección 13 NIIF para pymes. (2020)
The recognition of inventory costs in Colombian tax regulations and in the IFRS for SMEs for the use of small and medium-sized companies. These seek to simplify accounting requirements by making them less complex, reducing the cost and effort incurred in generating financial and fiscal information. The IFRS for SMEs standard contains section 13 that deals with inventories; It is a management system whose function is to organize the goods or elements that a company may contain. This document looks for the way to explain the recognition and measurement of the cost of inventories, under written sources, that allows describing the adaptation in the management of the companies, for the presentation of the Financial Statements and income statement by making it a tool financial that generates a control that can be carried out daily.